Niat Beli Sepatu Merek Lokal oleh Generasi Muda: Pengaruh Consumer Ethnocentrism, Perceived Quality, Perceived Price, dan Perceived Brand Image - Maghfiroh, Lailatul; Iriani, Sri Setyo (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
Indonesia is one of the top 4 world footwear producers. On the other hand, there are many well-known foreign brand shoes in Indonesia. Ventela is one of a famous shoes local brand in Indonesia. The local consumers have preferences concerning the shoe producer country of origin. Local people prefer to buy local brand shoes if they have an ethnocentric taste and good perceptions about the local brand. Therefore, this study aims to determine the effect of consumer ethnocentrism, perceived quality, perceived price, and perceived brand image toward a willingness to buy Ventela shoes. The survey was conducted using an online questionnaire and collected data from 205 young generations. Multiple linear regression in SPSS software was used to analyze the collected data. This study shows that consumer ethnocentrism, perceived quality, and perceived price significantly affected willingness to buy. Meanwhile, the perceived brand image had no significant effect on willingness to buy. Further research is suggested to compare several local fashion brands with different positioning. The results of this study can be used as input for Ventela shoes in facing business competition and business development by paying attention to the variables used.